A multi layered encryption framework using intuitionistic fuzzy graphs and graph theoretic domination for secure communication networks - A. Meenakshi; S. Dhanushiya; Leo Mrsic; Antonios Kalampakas; Sovan Samanta (Scientific Reports)
Abstract Secure communication is essential in today’s rapidly evolving digital environment, and strong encryption methods are required to protect private data from unwanted access. The aim of this study is to strengthen the security and complexity of encrypted communications by adopting a new form of cryptographic encryption technique based on the principles of an intuitionistic fuzzy graph. Key graph-theoretic measures, such as domination number, vertex categorization (alpha-strong, beta-strong, and gamma-strong), vertex order coloring, and chromatic number, play important roles in this process. Domination number finds the key vertices of the network, while vertex strength categorization and fuzzy graph coloring provide multiple encryption layers, hence the encoded message is highly resistant to decryption unless a proper key is used. The chromatic number offers further security through various patterns of vertex coloring. The comparative analysis shows the proposed approach to be superior compared to RSA, AES, ECC, and Blowfish due to its increased security, computational efficiency, and resilience to attacks. This framework can be applied to the protection of banking PINs, military access codes, government identification numbers, cryptographic keys, and medical records, so it is an extremely versatile solution for protecting sensitive data. This multi-step approach to encryption through the proposed technique ensures safe transfer and efficient encoding as it establishes a complicated framework.